P-426 Placental pathology following Intrauterine Insemination (IUI) with or without Ovarian Stimulation (OS). (30th June 2022) - Souter, I; Cherouveim, P; Fitz, V; Hammer, K; Jiang, V; Sacha, C; Dimitriadis, I; Bormann, C; James, K; Roberts, D
Abstract: Study question: Do placental weight percentiles (PW %iles) and abnormality rates (PAR) differ in singleton-livebirths following IUI with or without OS [oral medications (OM), and injectable gonadotropins]? Summary answer: Following singleton-livebirths, PW did not differ between groups, albeit over half of placentas were ≤25 th %ile. Placental anatomic abnormalities were more often seen in OM cycles. What is known already: ART data suggest a possible association between stimulation-induced supraphysiologic estradiol levels and increased risk of placental abnormalities, as well as subsequent placental-mediated pregnancy complications, such as preeclampsia. Whether there is an association between OS protocols for IUI and placental pathology remains unknown. Study design, size, duration: Data from 975 IUI(±OS) cycles resulting in singleton livebirths at a large academic fertility center between 01/2004 and 01/2021, were retrospectively reviewed. In 386 cycles a full placental pathologic examination was available. Placentas were stratified by OS regimen into three groups: gonadotropins  (n = 222), OM  [Clomiphene Citrate (CC)/Letrozole (LTZ); n = 129], and unstimulated / natural  (n = 35). PW and PAR were compared between groups. Participants/materials, setting, methods: Participants: Women delivering a singleton liveborn following IUI(±OS) treatments with placental pathology available. Outcome Measures: PW (grs & %iles), and PAR (classified as anatomic, inflammatory, infectious, and vascular/thrombotic ). Statistics: Regression analysis was utilized to compare PW and PAR between groups, adjusting for potential confounders (PW: maternal and gestational age, BMI, infertility diagnosis, medical complications, infant gender; PAR: maternal and gestational age, BMI, race). Adjusted Odds Ratios (adjOR, 95%CI) were calculated for the latter. Main results and the role of chance: Mean(±STDEV) PW (grs) were 451.7(±113.3), 449.2(±102.4), and 481.8(±99.8), for the gonadotropins, OM, and natural groups, respectively. Interestingly, over half of the placentas in all three groups were ≤25 th %ile (58.6%, 56.1%, and 52.9%, for gonadotropins, OM, and natural, respectively, p=.249), while 41.8%, 46.4%, and 38.2% were below the 10 th %ile (for gonadotropins, OM, and natural, respectively, p=.598). Adjusted PW differences, and adjOR for small placenta (≤10 th %ile) did not differ between groups [PW OR(95%CI): 5.6(-17.9-29.2), -28.1(-71.4-15.2), -11.7(-52.6-29.3); small placenta OR(95%CI): 1.04(0.62-1.76); 1.27(0.40-4.01), and 0.96(0.34-2.74) for OM vs. gonadotropins, OM vs. natural, and gonadotropins vs. natural, latter as ref. ]. Regarding PAR, anatomic (43.7%, 52.7%, and 40%, p=.192), inflammatory (20.7%, 27.1%, and 20%, p=.354), infectious (32.9%, 33.3%, and 31.4%, p=.978), and vascular/thrombotic (42.3%, 41.9%, and 42.9%, p=.993) abnormalities rates did not differ between gonadotropins, OM, and natural, respectively. AdjORs(95%CI) for inflammatory, infectious, and vascular/thrombotic abnormalities did not differ significantly between groups. However, anatomic abnormalities were more frequent among OM compared to gonadotropin and natural cycles [adjOR(95%CI): 1.76(1.06-2.91), p=.028, gonadotropins as ref. ; 2.52(1.05-6.05), p=.038, natural as ref .]. Limitations, reasons for caution: This study is limited by its retrospective nature. Unfortunately, placental pathology was available only in conceptions clearly identified as resulting from IUI(±OS) treatments. However, birth weights did not differ between those with and without available placental pathology. Natural/IUI cycles were limited in numbers not allowing meaningful conclusions. Wider implications of the findings: Between IUI-conceived, singleton-livebirths with available placental pathology, mean PW did not differ significantly. However, a higher-than-expected percent of placentas were below the expected %iles, suggesting that IUI(±OS) might be associated with altered placental growth. Placental anatomic abnormalities were more common among OM cycles, compared to gonadotropins, and n atural IUI cycles. Trial registration number: Not applicable